"I question America…. is this America?" Learning to view the civil rights movement through an intersectional lens. Issue 3 (27th May 2019) - Vickery, Amanda E.; Salinas, Cinthia S.
Abstract: This qualitative case study investigates how two preservice elementary teachers crafted narratives of Black women in the Civil Rights Movement using an intersectional lens. Using Black feminism and Black critical patriotism as theoretical frameworks, the authors examine the process in which preservice teachers attempted to construct historical narratives using Crenshaw's framework of intersectionality. The preservice teachers used this framework to examine the intersecting identities and resulting experiences of women in the past and present in order to present a more complex narrative of the Civil Rights Movement to elementary students. This study is important because it helps preservice teachers and their students become conscious of the ways in which different people experience(d) the world based on intersecting identities as a way to promote empathy and critical citizenship.